Phytopharmacologic aspects of Canscora decussata Roem and Schult. - K, Sethiya Neeraj; M. B., Patel; S. H., Mishra (Pharmacognosy Reviews, 2010)
Nature is an inexhaustible source of secondary metabolites—different types of alkaloids, terpenoids, phenolics, and other classes of organic compounds. In the process of isolation, purifi cation and determination of the structures of lead, with their biological effectiveness, every type of experimental tool and strategy, known too and developed over the years by various practitioners. The present review is an attempt to compile information on various aspects of Canscora decussata, “Shankhpushpi” of Indian traditional system of medicine. The phytoconstituents, such as phenolic compounds, xanthones, and triterpenoids were isolated from different parts of the plant. The plant possesses immunomodulatory, analgesic, anticonvulsant, antitubercular, antiinfl ammatory, spermicidal, central nervous system–depressive, and cardiostimulant properties. Clinical trials of marketed formulation showed very encouraging results.
Keywords: Shankhpushpi; phenolic compounds; xanthones; triterpenoids